Prevention of health care-associated infections: knowledge and practices in resident physicians - Yagui Moscoso, Martin (2021)
Objectives. To determine level of knowledge and practices on the measures of prevention of infections associated with health care (HAI) and factors associated with in incoming resident physicians 2018 of a university of Lima, Peru. Methods. A validated questionnaire was applied to 171 resident physicians in a cross-sectional study. Variables studied were age, sex, time as a professional, previous training, origin, type of university of origin, among others. Results. It was observed that 52% are female, 49% had 2 or less years as a medical professional, 49% came from a university in the interior of the country, only 34% occupied a captive vacancy and 71.9% had previous training on HAI prevention measures. 83% of the incoming resident physicians studied showed a low level of knowledge about HAI prevention measures while 68.4% of the incoming resident physicians studied showed inappropriate practices on HAI prevention measures. When performing the multivariate analysis, it showed that entering a medicine specialty was associated with a lower risk of having low level of knowledge (OR: 0.32, 95% CI: 0.11-0.93). The bivariate analysis showed that the longest time as a professional was related to lower risk of having inappropriate practices, this being confirmed when performing the multivariate analysis (OR: 0.936, 95% CI: 0.89-0.99). Conclusions. There is a low level of knowledge about HAI prevention measures and a high proportion with inappropriate practices in incoming residents 2018 on HAI prevention measures. It was observed that the type of specialty is a factor associated with the level of knowledge and the time of professional experience is a factor associated with the type of practice.